Modified space vector strategy for three level T-type inverter to reduce common mode voltage - Le, Văn Tài; Nguyen, Văn An; Quach , Thanh Hải; Tran, Vĩnh Thanh; Do, Đức Trí; Huynh, Thị Thu Hiền (Journal of Technical Education Science, 2019)
In this paper, a modified space vector pulse-width modulation (MSVPWM) scheme for the three-level quasi-switched boost T-type inverter (TL-qSBT2I) to reduce common mode is presented. The Shoot through (ST) state is inserted into zero vector in order not to affect the output voltage. Modified space vector control method can reduce the RMS of common mode voltage (CMV) value up to 42.8% as compared to the conventional space vector control method. Furthermore, to reduce the current ripple of inductor input by using two high-frequency carriers vcar1 and vcar2, where vcar2 is generated by shifting vcar1 through 90°. To verify the modified space vector control method for TL-qSBT2I, simulation results have presented in this paper.